Driving Sustainable Innovation: Islamic Financial Literacy and Inclusion in the Five Southernmost Provinces of Thailand - Asas Worasutr; Stephen E. Little; Mohammed Abdel Haq (European Journal of Islamic Finance)
Financial literacy is increasingly recognised as enhancing access to financial services. The role of financial literacy in enabling individuals to make well-informed financial decisions is crucial. Financial inclusion ensures that individuals can participate in the formal economy and access financial tools to improve their living standards. Accordingly, financial literacy and inclusion are essential because they provide people with the knowledge and access to services that promote a more sustainable financial system, which benefits the larger community and the economy. However, exploring Islamic financial literacy, particularly in Muslim minority countries, remains a nascent concept. Furthermore, research on financial literacy and inclusion from an Islamic perspective is limited. Therefore, this research aims to examine the level of Islamic financial literacy, inclusion, and their relationship in the five southernmost provinces of Thailand. A mixed-methods research design was employed, using questionnaires and semi-structured interviews to gather quantitative and qualitative data. Based on empirical evidence, proactive policy recommendations are proposed to encourage Islamic financial institutions to increase Islamic financial literacy and inclusion by educating their targeted customers and developing products tailored to their needs. This should also emphasise the significant contribution of higher education in implementing policies to educate and innovate Islamic financial products that are compatible with the community's requirements. To support these initiatives, more resources should be allocated to Islamic finance scholars to enable them to organise seminars to increase Islamic financial knowledge among the public. Additionally, an information centre could be established to gather statistical data related to the Islamic financial sector in a specific region to facilitate the creation of Islamic financial products that meet customers' demands.